2017
DOI: 10.1371/journal.pone.0181225
|View full text |Cite
|
Sign up to set email alerts
|

Brain synchronization during perception of facial emotional expressions with natural and unnatural dynamics

Abstract: Research on the perception of facial emotional expressions (FEEs) often uses static images that do not capture the dynamic character of social coordination in natural settings. Recent behavioral and neuroimaging studies suggest that dynamic FEEs (videos or morphs) enhance emotion perception. To identify mechanisms associated with the perception of FEEs with natural dynamics, the present EEG (Electroencephalography)study compared (i) ecologically valid stimuli of angry and happy FEEs with natural dynamics to (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
(96 reference statements)
0
9
0
1
Order By: Relevance
“…In addition to the open question whether or not PD patients have impaired face expression processing, these previous studies have two important limitations: first, they solely used static stimulus presentation and, second, they relied only on the six basic facial expressions. Concerning the first point, a series of recent studies has shown, however, that perception of facial expressions when presented in their real-life dynamic form (Bülthoff et al, 2011), results in significantly different performance patterns (Ambadar et al, 2005; Cunningham and Wallraven, 2009) as well as involvement of different brain areas (Kilts et al, 2003; Sato et al, 2004; Yoshikawa and Sato, 2006; Trautmann et al, 2009; Perdikis et al, 2017) compared to processing of static expressions. The second, important aspect that has been neglected in previous studies is that in daily life, expressions do not only consist of the six basic expressions, but they also include a much wider range of communicational, conversational, and emotional expressions and facial gestures such as tiredness, boredom, flirting, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the open question whether or not PD patients have impaired face expression processing, these previous studies have two important limitations: first, they solely used static stimulus presentation and, second, they relied only on the six basic facial expressions. Concerning the first point, a series of recent studies has shown, however, that perception of facial expressions when presented in their real-life dynamic form (Bülthoff et al, 2011), results in significantly different performance patterns (Ambadar et al, 2005; Cunningham and Wallraven, 2009) as well as involvement of different brain areas (Kilts et al, 2003; Sato et al, 2004; Yoshikawa and Sato, 2006; Trautmann et al, 2009; Perdikis et al, 2017) compared to processing of static expressions. The second, important aspect that has been neglected in previous studies is that in daily life, expressions do not only consist of the six basic expressions, but they also include a much wider range of communicational, conversational, and emotional expressions and facial gestures such as tiredness, boredom, flirting, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, participants differ in their response to static stimuli compared to dynamic stimuli. Participants report higher levels of arousal to a dynamic image (a neutral face morphing into an emotional face) than to a static image of an emotional face (Sato & Yoshikawa, 2007 as cited in Perdikis et al, 2017). When completing an emotion perception task with dynamic stimuli, participants were more accurate than those with static stimuli (Ambadar et al, 2005 as cited in Perdikis et al, 2017).…”
Section: Stimuli Used Within the Literaturementioning
confidence: 99%
“…Participants report higher levels of arousal to a dynamic image (a neutral face morphing into an emotional face) than to a static image of an emotional face (Sato & Yoshikawa, 2007 as cited in Perdikis et al, 2017). When completing an emotion perception task with dynamic stimuli, participants were more accurate than those with static stimuli (Ambadar et al, 2005 as cited in Perdikis et al, 2017). Participants also elicit greater facial mimicry to dynamic than static stimuli (Rymarczyk et al, 2011;Sato et al, 2007).…”
Section: Stimuli Used Within the Literaturementioning
confidence: 99%
“…Например, компьютерная анимация, при которой изменения лица происходят по кратчайшей прямой, приводит к замедленному и менее точному распознаванию эмоций, а также к более низким оценкам интенсивности, искренности и типичности по сравнению с действительным развертыванием экспрессии [38; 130]. В силу нелинейности и асинхронии активности мимических мышц при переживании эмоции [88], естественные динамические экспрессии и переходы между ними воспринимаются иначе, чем искусственные динамические последовательности, созданные путем линейного морфинга [81], и приводят к различиям в волновой активности головного мозга [103]. Точность категоризации снижается при инверсии естественных видеофрагментов во времени [81; 107].…”
Section: специфика восприятия экспрессий подвижного лицаunclassified